Improving Breakdown Voltage for a Novel SOI LDMOS with a Lateral Variable Doping Profile on the Top Interface of the Buried Oxide Layer - Jingjing Jin; Shengdong Hu; Yinhui Chen; Kaizhou Tan; Jun Luo; Feng Zhou; Zongze Chen; Ye Huang (Advances in Condensed Matter Physics)
In order to achieve a high breakdown voltage (BV) for the SOI (Silicon-On-Insulator) power device in high voltage ICs, a novel high voltage n-channel lateral double-diffused MOS (LDMOS) with a lateral variable interface doping profile (LVID) placed at the interface between the SOI layer and the buried-oxide (BOX) layer (LVID SOI) is researched. Its breakdown mechanism is investigated theoretically, and its structure parameters are optimized and analyzed by 2D simulation software MEDICI. In the high voltage blocking state, the high concentration ionized donors in the depleted LVID make the surface electric field of SOI layer (ES) more uniform and enhance the electric field of BOX layer (EI), which can prevent the lateral premature breakdown and result in a higher BV. Compared with the conventional uniformly doped (UD) SOI LDMOS, EI of the optimized LVID SOI LDMOS is enhanced by 79% from 119 V/μm to 213 V/μm, and BV is increased by 33.4% from 169 V to 227 V. Simulations indicate that the method of LVID profile can significantly improve breakdown voltage for the SOI LDMOS.